ANALISA KEBERADAAN MASYARAKAT HUKUM ADAT DI INDONESIA - Santriawan Mangumpaus; Yana Sukma Permana (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
The existence of Indigenous Peoples (MHA) is recognized and respected by the State through Article 18B of the 45 Constitution. therefore the government is obliged to protect the existence of indigenous peoples. However, the development of today's modern society has even negated the existence of indigenous peoples. The existence of massive population movements and land titling causes individualism to undermine the existence of indigenous and tribal peoples. Therefore, this research will answer whether the existence of MHA still needs to be protected by the government or does it have to change according to the times. Many regulations were launched to regulate MHA, which aims to protect MHA but these regulations by many observers still do not support the protection of MHA. The research method used is normative juridical research, which is a method that is carried out by examining library materials. From the various problems in the research area, it can be concluded that the existence of MHA will gradually become extinct. Article 18 B in the 1945 Constitution already implies the extinction of MHA with the clause